Tugas dan Wewenang Komisi Yudisial Jawa Timur dalam Pengawasan Hakim Tindak Pidana Korupsi - Musyafaah, Nur Lailatul (Al-Jinayah: Jurnal Hukum Pidana Islam, 2017)
Abstract: The duty of the East Java Regional Judicial Commission in the supervision of a corruption court judge is to receive community reports and court monitoring. The court monitoring was conducted on two matters, court monitoring based on community reports and on the initiative of the East Java Judicial Commission. The authority of the East Java Regional Judicial Commission in the supervision of a corruption judge is only authorized to receive reports, annotations, inspections and monitoring of the court session. The observation, examination, and proposal of sanction are done by Central Judicial Commission. In a juridical perspective, the duties and authorities of the East Java Judicial Commission on the judges of corruption crime have been in accordance with Article 20 of the Law of the Republic of Indonesia Number 18 in 2011 on Amendment to Law Number 22 in 2004 concerning Judicial Commission. Keywords: East Java Judicial Commission, Judges, Corruption. Abstrak: Tugas Komisi Yudisial Penghubung Wilayah Jawa Timur dalam pengawasan hakim pengadilan tindak pidana korupsi adalah menerima laporan masyarakat dan pemantauan persidangan. Adapun wewenang Komisi Yudisial Penghubung Wilayah Jawa Timur dalam pengawasan hakim tindak pidana korupsi adalah Komisi Yudisial Penghubung Wilayah Jawa Timur hanya berwenang menerima laporan, anotasi, pemeriksaan dan melakukan pemantauan persidangan. Adapun pengamatan, pemeriksaan, pengusulan sanksi dilakukan oleh Komisi Yudisial Pusat. Dalam perspektif yuridis, pelaksanaan tugas dan wewenang Komisi Yudisial Penghubung Wilayah Jawa Timur terhadap hakim pengadilan tindak pidana korupsi telah sesuai dengan Undang-Undang Republik Indonesia Nomor 18 Tahun 2011 Tentang Perubahan Atas Undang Nomor 22 Tahun 2004 tentang Komisi Yudisial. Kata Kunci: Komisi Yudisial Penghubung Wilayah Jawa Timur, Hakim, Tindak Pidana Korupsi.